Augmented reality applications as a digital learning innovation in response to the pandemic - Batool, Hira (Frontiers in Education, 2022)
Augmented applications are digital learning innovation that improves learning of the Thai students more rapidly in the virtual classrooms setting. Ever since the beginning of the covid, on-site teaching methods pushed back to avoid the spread of covid. This paper examines Thai college students’ attitude, subjective and behavioral norms regarding digital learning innovation through augmented application. The current study offered a theoretical model established through the theory of planned behavior to investigates Thai college students to choose augmented application as digital learning innovation in their course. The data was analyzed through structural equation modelling from 100 college students in Thailand. The findings of the paper showed that the college students’ acceptance toward digital learning innovation through augmented application can be explained through TPB wherever attitudinal and subjective factors showed signiﬁcant inﬂuence; henceforth, perceived behavioral control contributed insigniﬁcant influence. The findings acknowledge the digital learning innovation through augmented application from the Thai college students.